2019
DOI: 10.1038/s41559-019-0837-y
|View full text |Cite
|
Sign up to set email alerts
|

The spread of resistance to imidacloprid is restricted by thermotolerance in natural populations of Drosophila melanogaster

Abstract: Imidacloprid, the world's most utilised insecticide 1 , has raised considerable controversy due to its harmful effects on non-pest species 2-6 and there is increasing evidence showing that insecticides have become the primary selective force in many insect species [7][8][9][10][11][12][13][14] . The genetic response to insecticides is heterogeneous across population and environment [15][16][17] , leading to more complex patterns of genetic variation than previously thought. This motivated the investigation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 79 publications
(81 reference statements)
1
34
0
Order By: Relevance
“…The tradeoffs between alleles that confer thermotolerance and alleles that confer insecticide resistance may therefore restrict the frequency of insecticide resistance alleles in warmer areas. Taken together, these data suggest that temperature increase from climate change may restrict the spread of imidacloprid resistance in natural populations of D. melanogaster due to tradeoffs with thermotolerance . One of the important messages of this study is that tradeoffs between insecticide resistance and thermotolerance might not occur in a single gene or locus but could result from tradeoffs between different alleles of linked genes.…”
Section: Mechanisms Underlying How Climate Change Can Affect Insecticmentioning
confidence: 73%
See 4 more Smart Citations
“…The tradeoffs between alleles that confer thermotolerance and alleles that confer insecticide resistance may therefore restrict the frequency of insecticide resistance alleles in warmer areas. Taken together, these data suggest that temperature increase from climate change may restrict the spread of imidacloprid resistance in natural populations of D. melanogaster due to tradeoffs with thermotolerance . One of the important messages of this study is that tradeoffs between insecticide resistance and thermotolerance might not occur in a single gene or locus but could result from tradeoffs between different alleles of linked genes.…”
Section: Mechanisms Underlying How Climate Change Can Affect Insecticmentioning
confidence: 73%
“…In other cases, these tradeoffs or facilitations may not be the consequences of changes in a single locus. The comprehensive study of D. melanogaster from four different locations showed that reduced recombination due to chromosomal inversions may lead to linked genes or alleles which are inherited together . Such chromosomal blocks may contain alleles of genes that have opposite effects with regard to thermotolerance and insecticide resistance, leading to tradeoffs under the dual selection pressures of temperature and insecticide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations